Patient-centered priorities for improving medication management and adherence. Issue 1 (January 2015) - McMullen, Carmit K.; Safford, Monika M.; Bosworth, Hayden B.; Phansalkar, Shobha; Leong, Amye; Fagan, Maureen B.; Trontell, Anne; Rumptz, Maureen; Vandermeer, Meredith L.; Brinkman, William B.; Burkholder, Rebecca; Frank, Lori; et al.
Highlights The Centers for Education and Research on Therapeutics (CERTs) convened stakeholders including patients, providers, researchers and others to identify priorities for advancing patient-centered medication management. Stakeholders identified many priorities outside the traditional scope of adherence research. The top three priorities were: creating tools and systems to facilitate and evaluate patient-centered medication management plans; developing training on patient-centered prescribing for providers; and increasing patients' knowledge about medication management. Priorities differed across stakeholder groups. Notably, patients prioritized using peer support to improve medication management while researchers did not.